Kemandirian dan Minat Berwirausaha pada Mahasiswa Aktif Angkatan 2020 - Nabela Febika Areta Nanda; Niken Titi Pratitis; Isrida Yul Arifiana (Jurnal Psikologi Perseptual)
The decreasing number of jobs and the increasing number of students who are more oriented towards finding work have the potential to increase unemployment rates in the future. Students as people who will enter the world of work need an interest in entrepreneurship as a basis for opening new jobs. This study aims to see whether student independence is related to their interest in entrepreneurship. The design of this study is quantitative correlational with the Spearman's Rho analysis method. A total of 247 students were involved in this study, collected using quota sampling techniques taken from 2686 students of the 2020 intake of the Universitas 17 Agustus 1945 Surabaya with the calculation of the Isaac and Michael table. The measuring instruments used were the independence scale (α:0.932) and the entrepreneurial interest scale (α:0.944). The results of the study showed a positive correlation between the level of independence and students' entrepreneurial interest (r:0.993; p 0.001). A high level of independence makes students believe in their own abilities and not depend on external factors so that they can overcome thoughts about the risk of failure so that students become more interested in becoming entrepreneurs.